Capital Market Integration in the Pacific Basin Region : An Analysis of Real Interest Rate Linkages - Phylaktis, Kate (IMF Working Papers; Working Paper ;, 1995)
This paper investigates the extent to which financial markets in the Pacific Basin Region have become more integrated, by analyzing the comovements of real interest rates. The paper uses cointegration and error correction models and draws inferences on the degree of capital market integration by looking at the speed of adjustment of real interest rates following a shock. The results show that there has been an increase in capital market integration with both U.S. and Japan during the 1980s. Japan has not, however, overtaken U.S. in dominating the financial markets of these countries, except possibly in the case of Malaysia. Capital market integration is found to be greater in Singapore, Hong Kong and Taiwan Province of China. On the other hand, Japan is the least integrated country with the United States.